THE RANGE OF ADMINISTRATIVE JUSTICE SPECIALIZATIONS IN RUSSIA AND THE OTHER BRICS COUNTRIES - M. Kleandrov; I Pluzhnik (BRICS Law Journal, 2018)
This article deals with the challenges concerning increasing administrative justice efficacy in Russia and other BRICS countries, where the specialized development of jurisdictional bodies is inconsistent and far from effective. The article analyzes the gaps and disputed aspects of administrative justice including the mechanisms for judicial administrative dispute resolution in the BRICS countries. The authors argue that the level of effectiveness of administrative justice vested in judicial procedures depends critically on the specialization of the administrative courts. This involves individual judges, separately operating permanent judges, judicial committees, mono-courts, independent administrative judicial systems incorporated into larger judicial systems within the courts of general jurisdiction, and separate and independent administrative and judicial systems. Even though the BRICS countries do not have a structured administrative judiciary, the retrospective and comparative analysis of their administrative justice jurisdiction and its most effective practices and mechanisms undertaken by the authors enables them to rethink the existing approach to resolving administrative cases via the judiciary. The aim of the article is to initiate the creation of an independent administrative court system organization in order to ensure better justice in the areas of social life including legal relations with executive bodies. Suggestions for the implementation of the specialization of the administrative judiciary in the Russian Federation are given. The authors, for the first time in Russian jurisprudence, propose a theoretical model of an independent, four-tiered specialized legal mechanism of administrative justice, which includes the interrelated factors of court organization, the judiciary and their legal status. The range of the four specialized tiers of the administrative judicial system is proposed. It is argued that they should include a systematic succession represented by lower courts, first instance lower courts, area courts and a Higher Administrative Court of the Russian Federation.